Assesment of Viability of Sesame (Sesamum indicum L.) Seeds Using Germination Method with Paper Media - Mayasari Yamin; Sri Mulyani; S. Suhadi; Taufiq Hidayat RS (Agrotech Journal, 2022)
Seed viability is the ability of seed to germinate which is demonstrated by a variety of physiological or biochemical phenomena. Paper media can be used for testing seed viability. This study aimed to determine the most effective method of seed germination utilizing paper media for the viability of sesame seeds. The research was conducted at the Seed Laboratory of the Sweetener and Fiber Crops Research Institute, Malang in March – May 2020. The research method used a two-factor factorial Completely Randomized Design. The first factor was the sesame seed variety which consisted of SBR 1 and Winas 1. The second factor was the seed germination method which consisted of a test on top of paper, a test on rolled top papers, a test between of papers and a test between folded paper. Each treatment was replicated four times, resulting 32 experimental units. Sesame seed viability was significantly affected by the manner of seed germination using paper media, according to the findings. In comparison to other treatments, sesame seeds of the Winas 1 variety exhibited the highest percentages of simultaneous growth, germination, vigor index, normal seedling dry weight, hypocotyl length, and radicle length when tested on rolled top paper